PROFITABILITY ANALYSIS OF LONZA GROUP LIMITED - Kumar, B. Ravi; Sreedevi, K. (IJRDO - Journal of Business Management, 2015)
This paper is an endeavor to portray the profitability position of Lonza Group Limited. This casestudy is entirely based on secondary data. The data has been gathered from the annual reports ofthe company from 2009-2013. There are so many ratios that are available to analyze theprofitability position of a company. In this study few ratios like Gross Profit Ratio, operatingProfit Ratio, Net Profit Ratio, Return on Net worth (RONW) etc., were taken to determine theprofitability position of Lonza group Ltd.